A short history of the Russian Revolution - Swain, Geoffrey 1950- (Bloomsbury Academic, 2022)
"The 1917 Revolution sent shockwaves throughout the globe, setting a chain of events in motion that would change the entire course of the 20th century. With the overthrow of the Romanov Dynasty, Russia was plunged into the political unknown and, from the crucible of social unrest, ideological conflict and violent civil war, the world's first communist state was forged. This book provides an incisive overview of one of the most complex and turbulent periods in modern history, tracing key moments from the abdication of Tsar Nicolas II to the Bolshevik seizure of power. A leading authority on Russia and Eastern Europe, Geoffrey Swain highlights the important legacies of 1905, demonstrating how early revolutionary ambitions among the masses culminated in the events of 1917. Challenging conventions in Soviet scholarship, Swain argues that the Bolshevik concepts of discipline and ideology that had mobilised the revolution, set an unnecessary course towards dictatorship and terror. Attentive to new historiography in the field, this revised edition places a renewed emphasis on the social and cultural upheaval exMEperienced in Russia amid the nation's political turmoil"
Keywords: Februarrevolution -- 1917; Oktoberrevolution; Russland; Soviet Union / History / Revolution, 1917-1921; URSS / Histoire / 1917-1921 (Révolution); Soviet Union; 1917-1921; History